Aplikasi Dashboard Untuk Monitoring Lokasi dan Pengguna Parkir Berbasis Konsep MVC - Abd Rahman; Handrie Noprisson (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
The research aimed to develop a web-based parking dashboard application capable of integrating transaction data, membership management, parking slot monitoring, and real-time income reporting. The study was conducted at two parking management locations of PT. Oxient Konsultan Indonesia, namely True-Blue Hotel Cikini (Jakarta) and Intermark BSD (Tangerang). The research lasted for six months, from September to February 2025, with stages including literature study, application requirements analysis, application design, code development, testing, and reporting. The application was developed using CodeIgniter 4 for application structure management, Bootstrap 5 for the user interface design, MySQL with phpMyAdmin for database management, and Chart.js for data visualization. Development was carried out in Visual Studio Code with XAMPP as the local server, using hardware with an Intel Core i5-1135G7 processor and 16 GB RAM. Based on the research findings, the parking management dashboard application featured login options for admins and operators, as well as membership and transaction management. Admins could add new members, while operators were only able to input vehicle entry and exit transactions. The application provided daily reports and a statistical dashboard to display vehicle and income summaries.